2020
DOI: 10.1063/5.0010219
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent inverse spin Hall effect in Co/Pt spintronic emitters

Abstract: In bilayers of ferromagnets and heavy metals, which form the so-called spintronic emitters, the phenomena of ultrafast demagnetization and the inverse spin Hall effect (ISHE) conspire to yield remarkably efficient emission of electric pulses in the THz band. Light-induced demagnetization of the ferromagnet launches a pulse of spin current into the heavy metal, wherein it bifurcates into a radiative charge transient due to the ISHE. The influence of temperature on this combined effect should depend on both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 28 publications
5
25
1
Order By: Relevance
“…( 1) also applies to this metallic bilayer as it relies on the spin-to-charge conversion in Pt to generate THz emission. In agreement with a previous report 39 , the amplitude of the THz pulse decreases with decreasing temperature and reaches a plateau at 50 K (Fig. 3d).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…( 1) also applies to this metallic bilayer as it relies on the spin-to-charge conversion in Pt to generate THz emission. In agreement with a previous report 39 , the amplitude of the THz pulse decreases with decreasing temperature and reaches a plateau at 50 K (Fig. 3d).…”
supporting
confidence: 93%
“…3d). This behaviour, which is associated with the intrinsic components of the spin Hall effect in Pt 39 , significantly differs to what is observed in our YIG|Pt sample, allowing us to exclude the influence of the Pt layer in our measured temperature dependence of the LSSE. We conclude therefore that our measurement probes the temperature dependence of the spin mixing conductance.…”
contrasting
confidence: 58%
“…The observed effect of magnetic field on the amplitude of generated THz pulses in the TbCo 2 /FeCo heterostructure reveals ISHE mechanism of the THz emission similar to that described in Refs. 15 , 32 . Light-induced demagnetization in the FeCo layer launches a pulse of spin current into the TbCo 2 and Ru layers (see Fig.…”
Section: Model and Discussionmentioning
confidence: 99%
“…[ 56 ] Furthermore, previous study reported that the demagnetization dynamics are temperature independent for Co film. [ 57 ] Therefore, the temperature dependence of ETHzpeak cannot be simply explained in terms of the magnetization varied with temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Our observation is basically consistent with recent reports on the temperature dependence of spin Hall resistivity of Pt layer. [ 57,59 ] We also would like to mention that with decreasing the temperature, the exchange coupling of FM/Mn 2 Au bilayer builds up, which was observed by an asymmetric shape of the hysteresis loops at low temperature. [ 52 ] A small modulation of the exchangeā€coupling strength at the interface between FM and AFM might lead to notable changes in magnetic properties.…”
Section: Resultsmentioning
confidence: 99%